Stromal uptake and transmission of acid is a pathway for venting cancer cell-generated acid - Hulikova, A; Black, N; Hsia, L; Wilding, J; Bodmer, W; Swietach, P (National Academy of Sciences, 2016)
Proliferation and invasion of cancer cells require favorable pH, yet potentially toxic quantities of acid are produced metabolically. Membrane-bound transporters extrude acid from cancer cells, but little is known about the mechanisms that handle acid once it is released into the poorly-perfused extracellular space. Here, we studied acid-handling by stromal myofibroblasts (colon cancer-derived Hs675.T, intestinal InMyoFib, embryonic colon-derived CCD-112-CoN), skin fibroblasts (NHDF-Ad) and colorectal cancer (CRC) cells (HCT116, HT29) grown in mono- or co-culture. Expression of the acid-loading transporter anion exchanger 2 (AE2; SLC4A2 product) was detected in myofibroblasts and fibroblasts, but not in CRC cells. Compared to CRCs, Hs675.T and InMyoFib myofibroblasts had very high capacity to absorb extracellular acid. Acid-uptake into CCD-112-CoN and NHDF-Ad cells was slower and comparable to levels in CRCs, but increased alongside SLC4A2 expression under stimulation with transforming growth factor β1 (TGFβ1), a cytokine involved in cancer-stroma interplay. Myofibroblasts and fibroblasts are connected by gap junctions formed by proteins such as connexin-43 which allows the absorbed acid-load to be transmitted across the stromal syncytium. To match the stimulatory effect on acid-uptake, cell-to-cell coupling in NHDF-Ad and CCD-112-CoN cells was strengthened with TGFβ1. In contrast, acidtransmission was absent between CRCs, even after treatment with TGFβ1. We propose that the juxtaposition of an acid-absorbing myofibroblast syncytium and acid-producing CRCs improves the flow of acid through solid tumors. Importantly, the activities of stromal AE2 and connexin-43 do not place an energetic burden on cancer cells, allowing resources to be diverted for other biological functions such as growth.